Architectural Katas, April - May 2021 - Ford, Neal (O'Reilly Media, Inc., 2021)
About Architectural Katas: What could be better than practicing software architecture with your handpicked dream team of architects? Participants in Architectural Katas, moderated by Neal Ford, work together virtually in small groups of their choosing to solve a challenge an actual organization is facing. Everyone gets the chance to practice their craft with a real software architecture problem in a safe and social environment, and the finalists and winners earn well-deserved bragging rights (not to mention an intriguing line on their résumé). Plus a selected organization working for social good will have some of its gnarliest software architecture problems solved. What you'll learn-and how you can apply it Identify and design architectural components Explore techniques to analyze and select the right architecture patterns Learn how to diagram and document an architectural solution Develop better communication skills to champion architecture decisions to developers and stakeholders This training course is for you because... You're a senior-level developer who wants to make the move to architect. You're a practicing software architect who wants to hone your skills and learn new software architecture techniques and practices. You're responsible for creating a software architecture for your company, and you want to practice with a real-world challenge. Prerequisites Have a pen and paper handy to capture notes, insights, and inspiration Recommended follow-up: Read Fundamentals of Software Architecture (book) Read Building Microservices , second edition (book) Read Building Evolutionary Architectures (book) Read Building Event-Driven Microservices (book).